Electromyography of crural and pedal muscles in tufted capuchin monkeys (Sapajus apella): Implications for hallucal grasping behavior and first metatarsal morphology in euprimates. Issue 4 (18th February 2015) - Patel, Biren A.; Larson, Susan G.; Stern, Jack T.; Lewton, Kristi; Nalley, Thierra K.
ABSTRACT A hypertrophied peroneal process of the hallucal metatarsal, as seen in prosimians, has been linked to a powerful hallucal grasp via the contraction of the peroneus longus (PL) muscle causing adduction of the big toe. Electromyography (EMG) studies of lemurs and lorises, however, have concluded that PL is not substantially recruited during small branch locomotion when powerful hallucal grasping is needed most, and have suggested that there is no link between PL activity and peroneal process size. If this is correct, then we should also observe no change in PL activity when strong hallucal grasping is required in anthropoids because they have a relatively smaller peroneal process for PL to act on. This study addresses this hypothesis by evaluating EMG of crural and pedal muscles in capuchins (Sapajus apella) walking on substrates of different diameters. During locomotion on the narrow substrate (3.1 cm) that should elicit a strong hallucal grasp, we observed an intense increased recruitment of adductor hallucis, but only sustained, rather than markedly increased, PL activity. This indicates that PL is not involved in powerful hallucal grasping in capuchins, and confirms similar findings previously documented in prosimians. We continue to reject the hypothesis that a large peroneal process is an adaptation for powerful grasping and further argue that its morphology may not be related to PL's ability to adduct the hallux at all. In addition, the morphology of the peroneal process should not be used to assess hallucal grasping performance in fossils. Am J Phys Anthropol 156:553–564, 2015. © 2015 Wiley Periodicals, Inc.